A maturidade da indústria 4.0 em uma indústria de eletroeletrônicos no Polo Industrial de Manaus – um estudo de caso - Brasil, Ângelo César Coppo (Brasil, 2024)
With the technological evolution, the industries need to reinvent themselves to be able to deal with the strong competitiveness in the market. industry 4.0 has become the primary factor to be the differential in manufacturing processes and, thus, serve the largest possible portion of customers without losing profits. industry 4.0 is already a reality, and the case study addressed in this article aims to measure the maturity of a company in the electronics and electronics sector installed in the manaus industrial center, through the PIMM 4.0 system, where two main dimensions of the model are assessed, together with its sub-dimensions, as well as the necessary improvement opportunities. the results show that the company is beyond the ideal to reach the most advanced level proposed by the model used.